Smartphone – a third eye of people with blindness - Beniwal, Abhijeet; Senjam, Suraj Singh (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
In the current plethora of the digital world, smartphones have become an integral part of our lives and act as an essential supportive device in executing daily living activities. Until now, most of us believe that smartphones are devices meant for people with a good sight and are not considered assistive devices for visually impaired individuals. It may not be an incorrect statement, particularly in lower-middleincome countries. It is a common presumption that the use of smartphones would need a good vision function, or how can they be used by people with vision loss? However, in the recent past, technological advancement has led to makeshift changes in the interfaces between humans and smartphones in terms of interaction. Instead of relying on vision function, gestures, and even sound, one can interact with a smartphone. For this, various special apps named third-party accessible applications are being developed by many computer engineers and information technology experts or designers. For example, the MANI (Mobile Aided Note Identifier) application helps to identify bank notes. The InstaReader or KiBo accessible app helps to read print materials by converting text to speech. The K-NFB reader converts text to braille or speech, improving access to mail, bills, medical reports, etc. (1, 2) Therefore, using such special accessible apps, a blind person can access print materials even if they are not braille texts. In addition, there are builtin features of smartphones, the so-called screen readers, such as TalkBack in Android and VocieOver in IoS phones, which further help to access various contents and information present in smartphones. In this way, a smartphone can act as a third eye for blind users. Among all smartphone users, including visually impaired people, these features would help them enhance their social participation, networking, and connectedness with the rest of the world.